2017
DOI: 10.1016/j.neurobiolaging.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Heightened cortical excitability in aged rodents with memory impairment

Abstract: Elevated excitability in the hippocampus has emerged as a key contributor to reduced memory function in aging and in cognitive impairment prodromal to Alzheimer’s disease. Here, we investigated the relationship between neural activity and memory in the hippocampus and a connectional cortical network using an aged rat model of individual differences for memory impairment. The expression of cFos was used as a measure of pharmacologically induced neural activity. Aged memory-impaired rats exhibited elevated cFos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 52 publications
14
59
1
Order By: Relevance
“…This finding was replicated in a recent study using a pharmacological stimulus to induce neuronal activation and detection of activity by expression of the immediate early gene, cFos (Fig. 2A) [22]. cFos was increased in aged memory-impaired rats relative to both young and aged unimpaired rats, exhibiting a tight correlation with memory status such that greater cFos expression in CA3 coincided with poorer memory among the animals in the aged cohort.
Fig.
…”
Section: Hyperactivity In the Hippocampal Memory System Is Localized supporting
confidence: 72%
“…This finding was replicated in a recent study using a pharmacological stimulus to induce neuronal activation and detection of activity by expression of the immediate early gene, cFos (Fig. 2A) [22]. cFos was increased in aged memory-impaired rats relative to both young and aged unimpaired rats, exhibiting a tight correlation with memory status such that greater cFos expression in CA3 coincided with poorer memory among the animals in the aged cohort.
Fig.
…”
Section: Hyperactivity In the Hippocampal Memory System Is Localized supporting
confidence: 72%
“…In addition, τ-PET signal seems to be detectable in multiple brain regions across functional networks simultaneously rather than in a step-wise manner, which is more supportive of selectively vulnerable brain systems being the etiology as opposed to seed-based templating, although, both mechanisms may occur simultaneously (Walsh and Selkoe, 2016). In this context, it should be noted that functionally connected brain systems, centered in the parietal and posterior cingulate regions, have been found to be abnormal in mouse models of age-related memory impairment, and that this functional stress is alleviated with therapies targeting brain circuits (Haberman et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Substantial previous work has shown that physiological characteristics of CA3 can distinguish between aged rats with impaired or unimpaired memory. Aged impaired rats have elevated CA3 activation, which leads to inability to remap CA3 place cells in novel contexts (Haberman et al, 2017;Wilson et al, 2005). They furthermore have reduced expression of genes related to synaptic plasticity in CA3 (Adams et al, 2001;Haberman et al, 2011Haberman et al, , 2013Smith et al, 2000).…”
Section: Discussionmentioning
confidence: 99%